Using the conceptual map as a teaching strategy to improve reading comprehension - Toro Soler, Cecilia; Cepeda Cepeda, Consuelo Esperanza; Gil Sánchez, Luz Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article aims to describe the educational context of reading comprehension of students in 3rd and 4th grade of the educational institution “Sergio Camargo” (Miraflores, Colombia). t is intended to demonstrate the effect between the use of conceptual maps and the improvement in the reading comprehension by means of the qualitative methodology, with a critical social approach and a design based on the research-action, it can be found that the first pedagogical character that stimulates students to emulate ideas and forms of reading comprehension, is the teacher, giving examples and organizing the exercises, in such a way that if this principal agent does not find adequate strategies to improve the process of reading comprehension and he does it in a monotonous way, implicitly makes reading and reading comprehension a duty and an obligation for children. Reading in this way generates a decrease in self-interest on the students, also making it difficult for learners the chance for them to capture their own ideas. In this sense, the use of concept maps as a strategy influences reading comprehension and helps improve academic performance in a positive way, predicting the success of students.